Counseling in maternal–fetal medicine: SARS‐CoV‐2 infection in pregnancy. (3rd May 2021) - Di Mascio, D.; Buca, D.; Berghella, V.; Khalil, A.; Rizzo, G.; Odibo, A.; Saccone, G.; Galindo, A.; Liberati, M.; D'Antonio, F.
ABSTRACT: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is a zoonotic coronavirus that crossed species to infect humans, causing coronavirus disease 2019 (COVID‐19). Despite a potentially higher risk of pregnant women acquiring SARS‐CoV‐2 infection compared with the non‐pregnant population (particularly in some ethnic minorities), no additional specific recommendations to avoid exposure are needed in pregnancy. The most common clinical symptoms and laboratory signs of SARS‐CoV‐2 infection in pregnancy are fever, cough, lymphopenia and elevated C‐reactive protein levels. Pregnancy is associated with a higher risk of severe SARS‐CoV‐2 infection compared with the non‐pregnant population, including pneumonia, admission to the intensive care unit and death, even after adjusting for potential risk factors for severe outcomes. The risk of miscarriage does not appear to be increased in women with SARS‐CoV‐2 infection. Evidence with regards to preterm birth and perinatal mortality is conflicting, but these risks are generally higher only in symptomatic, hospitalized women. The risk of vertical transmission, defined as the transmission of SARS‐CoV‐2 from the mother to the fetus or the newborn, is generally low. Fetal invasive procedures are considered to be generally safe in pregnant women with SARS‐CoV‐2 infection, although the evidence is still limited. In pregnant women with COVID‐19, use of steroids should not be avoided if clinically indicated; the preferred regimen is a 2‐day course of dexamethasone followed by an 8‐day course of methylprednisolone. Non‐steroidal anti‐inflammatory drugs may be used if there are no contraindications. Hospitalized pregnant women with severe COVID‐19 should undergo thromboprophylaxis throughout the duration of hospitalization and at least until discharge, preferably with low molecular weight heparin. Hospitalized women who have recovered from a period of serious or critical illness with COVID‐19 should be offered a fetal growth scan about 14 days after recovery from their illness. In asymptomatic or mildly symptomatic women who have tested positive for SARS‐CoV‐2 infection at full term (i.e. ≥ 39 weeks of gestation), induction of labor might be reasonable. To date, there is no clear consensus on the optimal timing of delivery for critically ill women. In women with no or few symptoms, management of labor should follow routine evidence‐based guidelines. Regardless of COVID‐19 status, mothers and their infants should remain together and breastfeeding, skin‐to‐skin contact, kangaroo mother care and rooming‐in throughout the day and night should be practiced, while applying necessary infection prevention and control measures. Many pregnant women have already undergone vaccination, mostly in the USA where the first reports show no significant difference in pregnancy outcomes in pregnant women receiving SARS‐CoV‐2 vaccination during pregnancy compared with the background risk. Vaccine‐generated antibodies were present in the umbilical cord blood and breast milk samples of pregnant and lactating women who received the mRNA COVID‐19 vaccine. Based on the available limited data on the safety of the COVID‐19 vaccine in pregnancy, it seems reasonable to offer the option of vaccination to pregnant women after accurate counseling on the potential risk of a severe course of the disease and the unknown risk of fetal exposure to the vaccine. © 2021 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Asesoramiento en medicina materno‐fetal: Infección por SARS‐CoV‐2 en el embarazo El coronavirus del síndrome respiratorio agudo grave 2 (SRAS‐CoV‐2) es un coronavirus zoonótico que ha contagiado a otras especies e infectado a los seres humanos, causando la enfermedad de coronavirus 2019 (COVID‐19). A pesar del riesgo potencialmente mayor de que las mujeres embarazadas adquieran la infección por el SRAS‐CoV‐2 en comparación con la población no embarazada (en particular en algunas minorías étnicas), no se necesitan recomendaciones específicas adicionales para evitar la exposición durante el embarazo. Los síntomas clínicos y los indicios de laboratorio más comunes de la infección por SRAS‐CoV‐2 en el embarazo son fiebre, tos, linfopenia y niveles elevados de proteína C reactiva. El embarazo se asocia a un mayor riesgo de infección grave por SRAS‐CoV‐2 en comparación con la población no embarazada, que incluye neumonía, ingreso en la unidad de cuidados intensivos y la muerte, incluso después de ajustar con respecto a los posibles factores de riesgo de resultados graves. El riesgo de aborto no parece ser mayor en las mujeres con infección por SRAS‐CoV‐2. La evidencia relativa al parto prematuro y a la mortalidad perinatal es contradictoria, pero estos riesgos suelen ser mayores sólo en las mujeres sintomáticas y hospitalizadas. El riesgo de transmisión vertical, definido como la transmisión del SRAS‐CoV‐2 de la madre al feto, o al recién nacido, es generalmente bajo. Las intervenciones traumáticas fetales se consideran generalmente seguras en las mujeres embarazadas con infección por el SRAS‐CoV‐2, aunque la evidencia es aún limitada. En las mujeres embarazadas con COVID‐19, no debe evitarse el uso de esteroides si está indicado clínicamente; el régimen preferido es un tratamiento de 2 días de dexametasona seguido de un tratamiento de 8 días de metilprednisolona. Si no hay contraindicaciones, se pueden utilizar antiinflamatorios no esteroideos. Las mujeres embarazadas hospitalizadas con COVID‐19 grave deben someterse a tromboprofilaxis durante toda la hospitalización y al menos hasta el alta, preferiblemente con heparina de bajo peso molecular. A las mujeres hospitalizadas que se han recuperado de un período de enfermedad grave o crítica con COVID‐19 se les debe ofrecer una exploración del crecimiento fetal unos 14 días después de haberse recuperado de su enfermedad. En las mujeres asintomáticas o ligeramente sintomáticas que han dado positivo en la prueba de infección por SRAS‐CoV‐2 a término ( es decir, ≥39 semanas de gestación), la inducción del parto podría ser aconsejable. Hasta la fecha, no existe un consenso claro sobre el momento óptimo para el parto de las mujeres en estado crítico. En las mujeres asintomáticas o con pocos síntomas, la atención durante el parto debe seguir las pautas rutinarias basadas en la evidencia. Independientemente del estatus de COVID‐19, las madres y sus bebés deben permanecer juntos y se debe practicar la lactancia materna, el contacto piel con piel, el cuidado madre canguro y mantener la cuna al lado día y noche, al tiempo que se aplican las medidas necesarias de prevención y control de infecciones. Muchas mujeres embarazadas ya han sido vacunadas, sobre todo en los Estados Unidos, donde los primeros informes no muestran diferencias significativas en los resultados del embarazo en las mujeres embarazadas que se vacunan contra el SRAS‐CoV‐2 durante el embarazo, en comparación con el riesgo de base. Se encontraron anticuerpos generados por la vacuna en las muestras de sangre del cordón umbilical y de leche materna de las mujeres embarazadas y lactantes que recibieron la vacuna de ARNm para COVID‐19. A partir de los limitados datos disponibles sobre la seguridad de la vacuna para COVID‐19 en el embarazo, parece razonable ofrecer la opción de la vacunación a las mujeres embarazadas después de un asesoramiento preciso sobre el riesgo potencial de una evolución grave de la enfermedad y el riesgo desconocido de exposición del feto a la vacuna . © 2021 Sociedad Internacional de Ecografía en Obstetricia y Ginecología. 摘要: 母婴医学咨询:怀孕期间的SARS‐CoV‐2感染 冠状病毒2严重急性呼吸系统综合征(SARS‐CoV‐2)是一种人畜共患的冠状病毒，其跨物种感染人类，导致2019年冠状病毒疾病爆发(COVID‐19)。尽管与未怀孕的人群(尤其是在某些少数族裔人群中)相比，孕妇感染SARS‐CoV‐2的风险可能更高，但怀孕期间无需额外的具体建议避免接触感染源。孕妇SARS‐CoV‐2感染最常见的临床症状和实验室表征是发烧，咳嗽，淋巴细胞减少和C反应蛋白水平升高。与非妊娠人群(包括肺炎，重症监护病房入院和死亡)相比，妊娠与严重的SARS‐CoV‐2感染风险较高相关，即使在调整了严重后果的潜在危险因素后也是如此。患有SARS‐CoV‐2感染的女性流产的风险似乎没有增加。关于早产和围产期死亡率的证据相互矛盾，但这些风险通常仅在有症状，住院的妇女中更高。垂直传播(定义为SARS‐CoV‐2从母亲向胎儿或新生儿传播)的风险通常较低。尽管证据仍然有限，但认为胎儿入侵性检查对患有SARS‐CoV‐2感染的孕妇通常是安全的。患有COVID‐19的孕妇，如果符合临床适应症，使用类固醇则不应当被避免。 优选的方案是地塞米松2天疗程，随后使用甲基泼尼松龙8天疗程。如果没有禁忌症，可以使用非甾体类抗炎药。住院的严重COVID‐19孕妇应在整个住院期间进行血栓预防治疗至少持续至出院前，最好使用低分子量肝素。从严重或重症COVID‐19疾病中康复的住院孕妇，应在疾病康复后约14天接受胎儿生长扫描。<14>在足月(即</ 14>≥<263>妊娠39周)SARS‐CoV‐2感染呈阳性的无症状或轻度症状的女性中，引产是较合理的。</ 263>迄今为止，对于重症孕妇的最佳分娩时间尚无明确共识。对于没有症状或症状很少的孕妇，分娩治疗应遵循常规的循证指南。不论COVID‐19状况如何，母亲和婴儿都应保持在一起及母乳喂养，并应用皮肤接触，袋鼠妈妈护理法则及全天候产房内护理方案，同时采取必要的感染防控措施。许多孕妇已经进行了疫苗接种，大部分在美国的第一份报告显示，与背景风险相比，怀孕期间接受SARS‐CoV‐2疫苗接种的孕妇的妊娠预后没有显着差异。接受mRNA COVID‐19疫苗的孕妇和哺乳期妇女的脐带血和母乳样品中均存在疫苗产生的抗体。根据现有的关于COVID‐19疫苗在妊娠中安全性的有限数据，在对严重病程的潜在风险和未知的胎儿病毒接触风险进行了准确的咨询之后，为孕妇提供疫苗接种选择似乎是合理的。